Failure of Polyethylene Inlays in Cementless Total Hip Arthroplasty: A Retrieval Analysis. (31st August 2016) - Mueller, Ulrike; Lee, Christoph; Heisel, Christian; Thomsen, Marc; Bitsch, Rudi G.; Kretzer, J. Philippe
Abstract : A retrieval analysis has been performed on 50 polyethylene inlays of cementless screw ring implants (Mecring, Mecron, Berlin, Germany) to investigate the failure mechanism of this specific open cup hip arthroplasty design that has shown a high clinical failure rate. Design-specific damage modes like rim creep, collar fatigue, and backside wear were assessed. Furthermore, the inlays were measured using a CMM to determine deformation. In 90% backside wear was observed and collar fatigue occurred in 68% of the cases. Rim creep was present in 38% of the polyethylene inlays. In 90% of the cases the cup opening diameter was 32.1 mm or less and 46% had a diameter less than 32 mm. It seems that creep and deformation of the polyethylene leads to a reduced diameter at the cup opening and consequently decreased clearance. To avoid this type of failure, polyethylene inlays should be supported at the back by the cup to reduce the risk of ongoing creep deformation.